Kajian Naskah Kitab Qawa’id al-‘Aqaid Wa Huwa Tsaaniy Min Kitab Ihya Ulumuddin Milik Sultan Mahmud Badaruddin II - Syukri, Ahmad; Habiburrahman, Habiburrahman (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2021)
Abstract The development of Palembang as a Malay Islamic civilized city that advanced in the early 19th century AD, one of which is drawn from the attention of the Sultan of Palembang to religious texts In this paper examines the description of the manuscript of the Kitab of Qowaidil Aqoid Ma Huwa Tsaniy min Kitab Ihya Ulumuddin owned by Sultan Mahmud Badaruddin II. The method of philology research uses a single edition model, using the workings of the diplomatic edition. This manuscript's writing in Arabic is included in Ilmu Kalam, which needs a particular explanation from Ulama Ilmu Kalam. The illumination of the manuscript appears simple, using European paper. From colophon, we can see the amount of attention and appreciation of Sultan Mahmud Badaruddin II to Palembang Sultanate collection's religious manuscripts.